Assessment of photobiomodulation effect on osteoblast-like MG-63 cell biological behavior: analyzing proliferation and migration in the absence or presence of nicotine - Zeinab Rezaei Esfahrood; Helia Sarlak; Maryam Torshabi; Serlie Hartoonian; Fatemeh Shekarchi (BMC Oral Health)
Abstract Background and aim Nicotine has adverse cellular and molecular effects on periodontal tissue and alveolar bone. Photobiomodulation therapy (PBMT) through cellular stimulation may be able to reverse the effects of nicotine on bone. This study examines the effect of Photobiomodulation therapy (PBMT) on the proliferation and migration of MG-63 osteoblast-like cells in the presence and absence of nicotine. Materials and methods The cytotoxic effects of 3 mM concentration and the protective effects of 660 and 808 nm low-level lasers on the MG-63 cell line were investigated and compared. Cell survival and proliferation were evaluated by the MTT assay (660 nm: Continuous, 150 mW, 0.5 cm², 240 mW/cm², 16 s, 4 J/cm², 808 nm: Continuous, 250 mW, 0.5 cm², 400 mW/cm², 10 s, 4 J/cm²), and cell migration was assessed by scratch test (660 nm: Continuous, 150 mW, 3 cm², 50 mW/cm², 200 s, 4 J/cm², 808 nm: Continuous, 250 mW, 3 cm², 83.3 mW/cm², 114 s, 4 J/cm²). Results The results of this study showed that 3 millimolar nicotine concentration has cytotoxic effects on the survival, proliferation, and migration of MG-63 cells (p < 0.05). Additionally, it was found that 660 nm and 808 nm low-level lasers alone or in combination could not increase survival and proliferation in MG-63 cells treated with nicotine (p < 0.05). However, the results demonstrated that PBMT with 660 and 808 nm lasers could increase cellular migration of MG-63 cells treated with nicotine (p < 0.05). Conclusion The results of the current study clearly demonstrate that PBMT, particularly 808 and 660 nms low-level lasers, are effective in improving the migration and repair of MG-63 cells treated with nicotine. However, they could not reduce the negative effects of nicotine on the survival and proliferation of MG-63 cells. Further research is essential to investigate the effects of PBMT on bone tissue healing and regeneration in smokers.